PRIORITAS KONSUMEN DALAM PEMBELIAN PRODUK BAKSO KEMASAN (STUDI KASUS PASAR TRADISIONAL WONOKROMO SURABAYA) - Kusuma, Andi; Nugroho, Sigit Dwi; Parsudi, Setyo (Berkala Ilmiah AGRIDEVINA, 2017)
The development of consumer knowledge on purchased product includes severalcharacteristics which has to be fulfilled by producers. It becomes an important demandfor complete and clear information on purchased product which can include productbrand, quality, nutrition, and halal certificate the research took 3 kinds of packagingmeatball which was available in traditional market such as Yikko, KJM “Kijang Mas”,and AJ. This research was conducted to understand characteristic of the packagingmeatball consumer and to understand the relation between variabel and preference alsoto understand which attribute was considered important according to consumer inWonokromo traditional market. The sampling technique was conducted by nonprobability sampling through the accidental sampling method and the data analysis useddescriptive analysis, IPA (Important Performance Index). There were several similiaritiesof meatball consumer, such as: was dominated by women with average age was 17 – 24years old and was moeslem which were mostly student, private employee, housewife, andentrepreneur. The income level was around Rp 1.000.001 – Rp. 3.000.000 with the lasteducation level was SMU/SMK. The most important attribute according to consumerwere price, suppleness, flavor, halal certificate, quality and the less important attributefor consumer was composition. The attribute of packaging meatballs had a significantrelation to consumer preference such as price, flavor, suppleness, and quality. Price wasthe most important considerable attribute for consumer on purchasing because incomefactor which was classified to low medium income in Wonokromo traditional marketSurabaya.